53rd AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference<BR&amp;gt;20th AIAA/ASME/AHS Adapti 2012
DOI: 10.2514/6.2012-1476
|View full text |Cite
|
Sign up to set email alerts
|

Actuator Bonding Optimization and System Control of a Rotor Blade Ultrasonic Deicing System

Abstract: The use of ultrasonic excitation has shown the ability to promote ice shedding of impact ice (<2 mm thick) during prior wind tunnel testing efforts. The ultrasonic deicing technology is implemented to structures representative of rotorcraft blade leading edges and tested under impact icing and centrifugal environments (390 gs). Finite Element Models (FEM) are experimentally validated and used to predict the ultrasonic ice shedding transverse shear stresses responsible for ice shedding. The FEM tools are then u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In order to develop models for the design and analysis of piezoelectric systems, it is interesting to determine the main physical effects involved in de-icing. Many authors have set up video recordings [12][14] [22] during their tests. The speed of the fracture phenomena, with time constants lower than milliseconds, is emphasized by the use of fast video cameras.…”
Section: Modeling Of Piezoelectric De-icing Systems: State Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop models for the design and analysis of piezoelectric systems, it is interesting to determine the main physical effects involved in de-icing. Many authors have set up video recordings [12][14] [22] during their tests. The speed of the fracture phenomena, with time constants lower than milliseconds, is emphasized by the use of fast video cameras.…”
Section: Modeling Of Piezoelectric De-icing Systems: State Of Thementioning
confidence: 99%
“…The two phenomena can be consecutive without interruption or can require an increase in voltage magnitude or change of frequency to occur after a first fracture. In the tests reported in the literature, the activation of the support is generally carried out by a sweep over the frequency ranges that can excite extensional [6].. [12] or flexural [13].. [15][22] modes. For all of these modes, it is possible to note a change in the resonance frequency with the thickness of the ice and a significant amplification of the vibrations at resonance.…”
Section: Modeling Of Piezoelectric De-icing Systems: State Of Thementioning
confidence: 99%
“…Palacios initiated many studies on de-icing systems [16] [21] and tested several technologies. For piezoelectric de-icing systems, he used piezoelectric patches to generate ultrasonic shear stress at high frequency (around a few tens of kHz).…”
Section: Electromechanical De-icing Systemsmentioning
confidence: 99%
“…In [20], experiments showed two main failures related to the bonding of the actuators: fracture of the piezoelectric ceramic at the solder joint location and delamination between the ceramic and the host. To tackle this problem, Palacios proposed optimizing the bonding of the supply wire on the ceramic and the bonding between the piezoelectric actuators and the substrate to avoid concentrations of stresses [21]. In [22], he also investigated the effect of hydrophobic coating combined with an ultrasonic deicing system and showed that the ice adhesion depended on the substrate roughness.…”
Section: Electromechanical De-icing Systemsmentioning
confidence: 99%
“…It has the disadvantage of a risk of mechanical failure for too high vibration levels. Palacios noted this type of failure in his publications and reports 12,13 . Table 3 shows the evolution of the characteristic quantities (frequency, voltage and power) leading to deicing for a beginning of delamination in one point and for a delamination over 55% of the surface.…”
Section: E Results On the Studied Configurationsmentioning
confidence: 89%